Liver Cirrhosis Debates and Current Challenges - Tsoulfas, Georgios (IntechOpen, 2019)
Liver cirrhosis and its complications affect millions of patients of all ages around the globe and present treating physicians with perplexing problems, given the variety of etiologies and the critical nature of hepatic physiology. This book is a collection of chapters offering the distilled knowledge of various worldwide experts in hepatic surgery and hepatic physiology. The various debates that are presented regarding the diagnosis and treatment of liver cirrhosis and its significant complications, in addition to the most up-to-date information regarding molecular aspects, provide the reader with the full spectrum of knowledge in this challenging and continuously evolving field.